Piezoelectric thin films: an integrated review of transducers and energy harvesting - Khan, Asif; Abas, Zafar; Soo Kim, Heung; Oh, Il-Kwon (Smart materials and structures, 2016)
Piezoelectric thin films offer a number of advantages in various applications, such as high energy density harvesters, a wide dynamic range, and high sensitivity sensors, as well as large displacement and low power consumption actuators. This review covers the available material forms and applications of piezoelectric thin films: lead zirconate titanate (PZT)-based thin films, lead-free piezoelectric thin films, piezopolymer films, cellulose-based electroactive paper (EAPap), and many other thin films used for electromechanical transduction. The electromechanical properties and performances of piezoelectric films are compared and their suitability for particular applications are reported. The key ideas of piezoelectric thin films are reviewed and discussed for sensory and actuation systems, energy harvesting, and medical and acoustic transducers. In the last section, an insight into the future outlook and possibilities for thin film-based devices and their integration into real-world applications is presented.